Cosmopolitanism and Oscillation in Orhan Pamuk’s My Name is Red - Catharina Brameswari (Journal of Language and Literature, 2020)
This research emphasizes on the challenges stemming from the attempts in inventing Turkey’s new ideal identity faced by the miniaturists in Orhan Pamuk’s My Name is Red. It focuses on the encounter and tension between the East and the West that is symbolized in the usage of the Italian Renaissance painting style by Turkish miniature painters. There are two issues discussed namely the East-West oscillation and the complex desire to imitate others. The miniaturists face the predicament in the development of Turkey’s new ideal identity, which is represented in the appropriation of the Italian Renaissance Painting. I employed library research which borrowed Said’s discourse on Orientalism and Bhabha’s Postcolonialism in order to dismantle the endless oscillation in My Name is Red. Through his work, Pamuk wants to emphasize his position for not taking sides. Additionally, he tries to raise his critic to Turkey’s abrupt modernization and suggests hybridity as the solution to the predicament of the East-West oscillation.